Politikai viták a Muraköz és a Muravidék visszacsatolásáról - Olasz, Lajos (Közép-Európai Közlemények, 2024)
During the German attack on April 6, 1941, Yugoslavia fell apart. The independent Croatian state was established. Hungarian forces occupied the territories annexed during the Trianon Peace Treaty of 1920 and introduced military administration in the Muravidék. However, the Croatian administration continued to operate in Muraköz, which has a largely Croatian population. The Budapest government would have handed over control of Muraköz to the Croats. In return, he asked for the recognition of Hungarian sovereignty, as well as Adriatic port and railway rights in Croatia. However, the Croatian government considered Muraköz as its own territory and did not want to give compensation for it. In the meantime, in Hungary, especially in Zala county, a broad social movement was started for the return of these areas. Abbot Joseph Pehm was at the head of the movement. He urged the introduction of military administration in the Muraköz, and then the transition to civilian administration. The government finally took these steps during the summer, and then in December the reintegration of the entire Délvidék was signed into law.